Direct computation of statistical variations in electromagnetic problems - Ajayi, Ajibola (2008)
This work described in this thesis develops a computationally efficient approach to performing electromagnetic simulations in the presence of statistically defined uncertainties caused by either material inhomogeneities, or fabrication and placement tolerances. Comparisons are made with results from Monte Carlo simulations and a sequence of higher order approximation extensions is considered.